Ideal Type of Islamic Healing in Indonesia: A Case Study on Pak Endog Alternative Islamic-Type Medication - Imzastini, Nur Qomariyah; Simatupang, Gabriel Roosmargo Lono Lastoro (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
The map of Islamic healing is often interpreted based only on the values of Islamic teachings. Some cultural and religious concepts and practices concerning spiritual or supernatural relationships are often ignored because they are contrary to the concept of Islamic teachings. This article analyzes the Islamic healing practiced in the socio-cultural life inherently. The religious space practice in terms of identification, healing and restoration of illness illustrates that the interaction between religion and culture is not rigid in addressing health and humanitarian issues. This article is based on field research at alternative healing in Tuban East Java which elaborated by enrichment of literary texts. The results of this study discuss various types of Islamic-based healing as alternative medicine that spreading in Indonesian culture. This study map analyzes the characteristics of Islamic healing, both Normative Islam and Cultural Islam. Both cannot be ignored as variants of religious and cultural practices in the health context.